Mineral Nutrition of Livestock (4th Edition) - Suttle, Neville F (CABI, 2014)
Reviewing progress in the mineral nutrition of livestock over the last 10 years has been complicated by a small fraction of the many new papers that addressed practical problems in a logical way and were subjected to rigorous peer review. The focus has been either on fundamental studies of molecular pathways or on commercially attractive nutritional supplements, bypassing the ‘middle-ground’ of basic mineral nutrition. Fundamental studies have rarely produced information that changes the way mineral imbalances are diagnosed, treated or avoided. Applied studies have been dominated by commercial interests and some published conclusions have been highly misleading, even those appearing in prestigious journals. Commercially biased experiments in mineral nutrition can be easily recognized: experimental designs follow practices adopted by QCs during cross examinations, avoiding questions to which the answer is unknown and possibly damning; statistical significance conventions are ignored, trends (P< 0.1) becoming ‘significant’ and if that ruse fails ‘numerical superiority’ may be claimed; positive comments about supplements are always mentioned in the abstract, however trivial; negative comments are avoided. One journal of human clinical nutrition now appends a ‘declaration of interest’ to their published papers, with an indication of what each author has contributed to minimize biased reporting, but commercial influences are now so pervasive that a similar declaration may be needed from referees. One veterinary journal now discriminates against citations of papers not subjected to peer review, a commendable practice that can greatly shorten reference lists. Rigorous review has led me to reject some widely held views, including those that unreservedly accredit selenomethionine and metal chelates with superior availability. While I think that Eric Underwood would have agreed with me, it seemed unfair to link his reputation to such contentious issues and a text which has continued to shift from the solid foundation that he so carefully laid in 1981. Two major changes in organization have been made: first, the complete separation of calcium from phosphorus, since they are mutual antagonists rather than bedfellows when it comes to non-ruminant nutrition; second, to provide a nutritional ‘heart’ to most chapters by tagging mineral requirements behind mineral composition and availability. To counter the growing separation of mineral nutrition in man and livestock, a final chapter has been added, which highlights areas of interdependence with implications for the health of both, and the sustainability of their shared environment.